2015
DOI: 10.1016/j.irfa.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of economic growth, oil prices, stock market depth, and other macroeconomic variables: Evidence from the G-20 countries

Abstract: This work is licensed under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International licence Newcastle University ePrints-eprint.ncl.ac.uk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 78 publications
1
49
0
Order By: Relevance
“…In the context of the framework described in Fig. 3, such Considering the impact of oil price on economic growth, Pradhan, Arvin and Ghoshray (2015) conclude with existence of long-run association for G20 countries. Though Difiglio (2014) reveals weakening role of oil price shocks in USA, Ito (2012) finds positive long-run effect of oil price changes on the growth in case of Russia.…”
Section: Resultsmentioning
confidence: 82%
“…In the context of the framework described in Fig. 3, such Considering the impact of oil price on economic growth, Pradhan, Arvin and Ghoshray (2015) conclude with existence of long-run association for G20 countries. Though Difiglio (2014) reveals weakening role of oil price shocks in USA, Ito (2012) finds positive long-run effect of oil price changes on the growth in case of Russia.…”
Section: Resultsmentioning
confidence: 82%
“…Also the information on the relationship between economic activity and stock market development can provide some implications for macroeconomic and development policy. As Pradhan et al (2015) and Kajurova and Rozmahel (2016), a sound and continued economic growth of countries can be promoted by stabilization of macroeconomic environment and the stock market development should be supported even in short-run. Finally, the investors and policy makers should be aware of the fact that the nature of the relationship can change over time and that the results should be regularly re-estimated.…”
Section: Resultsmentioning
confidence: 99%
“…The results of Sadorsky (1999) research confirmed that oil prices and oil price volatility have an important impact on real stock returns. Findings of Pradhan et al (2015), who used a panel The relationship between oil prices and exchange rates has been extensively studied over the last decade. Austvik (1987) examined the impact of changes in US dollar exchange rates on the oil market, suggesting that increase in the exchange rate of the dollar against other currencies leads to a lower oil price in dollars and vice versa.…”
Section: Literature Reviewmentioning
confidence: 99%